PHARMACEUTICAL WORLD WITH INNOVATIVE APPROACHES-A REVIEW - RASTOGI, HARSH; PURKAYASTHA, HRISHAV DAS; TIWARI, SHALINI (International Journal of Current Pharmaceutical Research, 2019)
An existing drug in the conventional dosage form is evolution in to novel drug delivery system which can significantly enhances and improves the performance of drug in terms of drug safety, drug efficacy as well as patient compliance. With the help of appropriate novel approaches, an existing drug molecule can get a new life and can be a major advance solution for the problems towards the release of drug at specific site and specific rate. The main aim of novel drug delivery system is to minimize the drug loss and drug degradation which can be achieved by targeting the drug to the site of interest. With the help of soluble or insoluble biodegradable natural and synthetic polymers different novel formulations can be formulated as microparticles, microcapsules, liposomes, neosomes, micelles etc. Targeting is based on active targeting and passive targeting mechanisms for drug release. This review covers the basic information on Novel Drug Delivery Systems (NDDS).